Paisagem urbana de Currais Novos: uma leitura a partir do Ensino de Geografia na Educação de Jovens e Adultos: EJA, com a utilização de Sequência Didática - Costa, Antônio Marcos de Morais (2024)
The study investigated the issues present in the teaching of Geography in the Youth and Adult Education (Educação de Jovens e Adultos - EJA) modality, highlighting high dropout rates and a lack of interest among working students, which directly impacts their academic and civic education. It presents a brief reflective overview of EJA in our country, emphasizing the structural and policy conditions required for its functioning, as well as the obstacles due to the lack of effective public policies that could ensure its operation and positively impact it, thereby addressing challenges that hinder student participation and learning. Starting from the central issue, student dropout and disengagement, the study suggested analyzing how the implementation of an integrated didactic sequence with a learning journal would influence the engagement and learning of students in the final years of elementary school in the EJA modality. Thus, the general objective of the research was to develop a didactic sequence, applied in EJA Geography classes, and supported by specific objectives: to assess the historical impacts and public policies directed at EJA, to create a didactic sequence and a learning journal for classroom use, and to implement the didactic sequence, with both in-school and field lesson times. The proposal was justified as a response to structural and temporary issues affecting the teaching of Geography in this modality, by proposing a comprehensive reflective action that builds alternative paths to the existing reality. In conducting the research, we employed documentary, bibliographic, exploratory, and field research. Considering the methodology for applying the sequence, we based it on a dialogical approach to the topic, production of didactic resources, writing, and field lessons guided by journal entries. The concept suggests the possibility of geographic education as a learning approach, designed to prepare students for understanding their role in (re)constructing the spatial setting in which they live. The emphasis of the field lesson was on the central urban space of Currais Novos (Rio Grandde do Norte State, Brazil). Throughout the educational journey, each participating student completed their journal, provided and instructed for use. The need for more comprehensive teacher training sensitive to the demands of EJA, as well as the importance of flexible and creative strategies to address educational challenges, the use of active methodologies, and the challenges of student attendance and retention are some of the conclusions highlighted in this report. In summary, the research aimed to overcome the obstacles faced in teaching Geography in EJA, promoting a deeper understanding of the concept of urban landscape and its interactions with students' lives, to make teaching more accessible, meaningful, and transformative, suggesting a viable and flexible learning alternative, which could be refined and applied in various teaching experiences in Brazilian EJA. Finally, the report presents a compilation of the findings, the experiences with the didactic sequence and journal, and the results obtained as a teacher-researcher, stemming from the immersion and completion of the study.